Effect of kurma ajwa extract (Phoenix dactylifera L.) on the growth of Candida albicans: Pengaruh estrak kurma ajwa (Phoenix dactylifera L.) terhadap pertumbuhan Candida albicans - Maqhfirah Amiruddin; Mohammad Dharma Utama; Andi Tenri Biba; Muhammad Jayadi Abdi,; Andi Wulan Ramadani (Makassar Dental Journal PDGI Makassar, 2024)
Candida albicans is the most common microorganism found in removable denture wearers. Dentistry has utilised natural herbal ingredients as antifungal-clinical alternatives. One of the developed herbal ingredients is ajwa kurma fruit (Phoenix dactylifera L.). This study was conducted to determine the effect of BKA extract on the growth of C.albicans with concentrations of 3.25%, 6.5%, 12.5%, 25%, and 50%. True experimental laboratory research with tests conducted in the laboratory with a research design in the form of posttest only design. The mean value of the smallest inhibition occurred in the 3.25% concentration treatment at 6.87 while the mean value of the largest inhibition occurred at a concentration of 50% at 8.31. With Kruskall wallis test obtained 0.000 (p-value <0.05). The mean value of the smallest killing power occurred at a 50% concentration of 0.00. It was concluded that the concentration of 3.25% ajwa date extract was the minimum inhibitory concentration and 50% concentration was the minimum kill concentration.